Effect of biosynthetic intermediates and citrate on the phenyllactic and hydroxyphenyllactic acids production by Lactobacillus plantarum CRL 778 - Dallagnol, Andrea Micaela (2011)
Aim: To evaluate the influence of biosynthetic precursors, intermediates and electron acceptors on the production of antifungal compounds [phenyllactic acid (PLA) and hydroxyphenyllactic acid (OH-PLA)] by Lactobacillus plantarum CRL 778, a strain isolated from home-made sourdough. Methods and Results: Growth of fermentative activity and antifungal compounds production by Lact. plantarum CRL 778 were evaluated in a chemically defined medium (CDM) supplemented with biosynthetic precursors [phenylalanine (Phe), tyrosine (Tyr)], intermediates [glutamate (Glu), alpha-ketoglutarate (α-KG)] and electron acceptors [citrate (Cit)]. Results showed that the highest PLA production (0·26mmoll -1), the main antifungal compound produced by Lact. plantarum CRL 778, occurred when greater concentrations of Phe than Tyr were present. Both PLA and OH-PLA yields were increased 2-folds when Cit was combined with α-KG instead of Glu at similar Tyr/Phe molar ratio. Similarly, glutamate dehydrogenase (GDH) activity was significantly (P<0·01) stimulated by α-KG and Cit in Glu-free medium. Conclusion: Phe was the major stimulant for PLA formation; however, Cit could increase both PLA and OH-PLA synthesis by Lact. plantarum CRL 778 probably due to an increase in oxidized NAD +. This effect, as well as the GDH activity, was enhanced by α-KG and down regulated by Glu. Significance and Impact of the Study: This is the first study where the role of Glu and GDH activity in the PLA and OH-PLA synthesis was evidenced in sourdough lactic acid bacteria (LAB) using a CDM. These results contribute to the knowledge on the antifungal compounds production by sourdough LAB with potential applications on the baked goods.